2013
DOI: 10.1073/pnas.1319000111
|View full text |Cite
|
Sign up to set email alerts
|

Dual-modality gene reporter for in vivo imaging

Abstract: The ability to track cells and their patterns of gene expression in living organisms can increase our understanding of tissue development and disease. Gene reporters for bioluminescence, fluorescence, radionuclide, and magnetic resonance imaging (MRI) have been described but these suffer variously from limited depth penetration, spatial resolution, and sensitivity. We describe here a gene reporter, based on the organic anion transporting protein Oatp1a1, which mediates uptake of a clinically approved, Gd3+-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 32 publications
1
129
0
Order By: Relevance
“…Known MRI reporter genes such as the chemical exchange saturation transfer reporter, transferrin receptor and ferritin have shown reproducibility from many research groups, but none have been able to overcome the sensitivity issues. 43 Recently, Patrick et al 44 investigated the feasibility of the OATP1A1 MRI reporter gene as a MRI reporter candidate. The authors transfected an OATP1A1-expressing vector into several cell lines including human embryonic kidney cells (HEK 293T), breast adenocarcinoma cells (MCF-7) and human colon adenocarcinoma cells (HCT 116), and confirmed the feasibility of OATP1A1 as an MRI reporter gene.…”
Section: Characterization Of Hepatocarcinoma Nodulesmentioning
confidence: 99%
“…Known MRI reporter genes such as the chemical exchange saturation transfer reporter, transferrin receptor and ferritin have shown reproducibility from many research groups, but none have been able to overcome the sensitivity issues. 43 Recently, Patrick et al 44 investigated the feasibility of the OATP1A1 MRI reporter gene as a MRI reporter candidate. The authors transfected an OATP1A1-expressing vector into several cell lines including human embryonic kidney cells (HEK 293T), breast adenocarcinoma cells (MCF-7) and human colon adenocarcinoma cells (HCT 116), and confirmed the feasibility of OATP1A1 as an MRI reporter gene.…”
Section: Characterization Of Hepatocarcinoma Nodulesmentioning
confidence: 99%
“…(16), providing a milestone in MR reporter systems. Although OATP1B1 and -3 both belong to the OATP family, they differ slightly.…”
Section: Discussionmentioning
confidence: 99%
“…OATP1B1 has been reported as a plasma membrane transporter for d -luciferin, the substrate of luciferase (36). The bioluminescence can be enhanced by overexpressing OATP1B1 for cell tracking (16). Our study showed that OATP1B3 overexpression would facilitate the cellular uptake of d -luciferin, and this phenomenon was repressed by OATP1B3 inhibitor, rifampicin (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another early example was beta galactosidase, which cleaves a sugar group from a specially designed Gd 3+ chelate, thereby unblocking water accessibility and increasing T 1 relaxivity [42]. Other reporters have been based on proteins that transport paramagnetic species such as Mn 2+ [11], gadolinium chelates [43], transferrin [44, 45] or ferritin [46] into cells or trap small molecule CEST reporters [47]. Alternatively, proteins have been engineered to display biotin on the cell surface, allowing binding and accumulation of an inorganic imaging agent linked to a biotin-binding protein such as streptavidin or transferrin [48, 49].…”
Section: Established Mechanisms Of Biomolecular Mri: T1 T2 Cestmentioning
confidence: 99%